The Role of Character Development through Physical Education Learning in Preventing Bullying among Students: Systematic Literature Review - Ariansyah, Ariansyah; Warni, Herita (PENJAGA : Pendidikan Jasmani dan Olahraga, 2026)
Bullying remains a prevalent issue across various levels of education and has negative impacts on students' social, psychological, and academic development. Physical Education, Sports, and Health (PJOK) has the potential to serve as a medium for character development to prevent bullying behavior through physical activities and social interactions. This study aims to analyze the role of character development through Physical Education learning in preventing bullying among students. The study employed a Systematic Literature Review (SLR) method based on the PRISMA guidelines. Literature searches were conducted through Google Scholar, Scopus, PubMed, and Semantic Scholar, covering publications from 2016 to 2026. A total of 17 articles that met the inclusion criteria were analyzed using thematic synthesis. The findings indicate that character development through Physical Education effectively enhances empathy, responsibility, cooperation, and prosocial behavior while reducing aggressive behavior and bullying. The results also highlight the important role of teachers, character-based instructional models, and innovative learning media in creating a safe and inclusive school environment. Therefore, Physical Education plays a strategic role in bullying prevention through strengthening students' character development.